Shifting taxes from labour to property: A simulation under labour market equilibrium - Flavia Coda Moscarola; Ugo Colombino; Francesco Figari; Marilena Locatelli (University of Essex, Institute for Social and Economic Research (ISER), 2014)
A tax shifting from labour income to housing taxation is generally advocated on efficiency grounds. However, most of the empirical literature focuses on the distributional implications of property tax reforms without paying much attention to potential consequences on the labour market. The aim of this paper is to fill this gap by investigating the effects of a tax shifting from labour income to property, guaranteeing revenue neutrality, and to assess the consequences of labour market equilibrium, both on occupation rates and income distribution. We propose to consider a hypothetical tax reform in Italy which uses the revenue of the tax on house property (actually implemented in 2012) for increasing tax credits on low incomes and making them refundable. In order to evaluate the reform we have developed a structural model of household labour supply which takes into account the labour market equilibrium conditions. Overall, the simulated policy provides a more effective income support and better incentives to work for low wage households and determines an improvement in inequality indexes.
Keywords: C35; C53; D31; J22; H31; 330; labour supply; tax shifting; personal tax on labour income; property tax; labour market equilibrium; microsimulation